A new technique for reducing accumulation, transport, and toxicity of heavy metals in wheat (Triticum aestivum L.) by bio-filtration of river wastewater. (May 2022) - Awan, Samrah Afzal; Khan, Imran; Rizwan, Muhammad; Ali, Zeshan; Ali, Shafaqat; Khan, Naeem; Arumugam, Natarajan; Almansour, Abdulrahman I.; Ilyas, Noshin
Abstract: The occurrence of contaminants such as heavy metals in an aqueous environment has become a global concern. In the present study, a bio-filter was designed to eliminate heavy metals from river wastewater contaminated with industrial effluents. Moreover, we analyzed simple tap water, bio-filtered water, and unfiltered river wastewater and measured the concentrations of different heavy metals in the samples, such as cadmium (Cd), nickel (Ni), lead (Pb), and copper (Cu). The current experiment explored irrigation effects of three water regimes (tap water, bio-filtered water, and wastewater) on two wheat ( Triticum aestivum L.) varieties (NARC-2009 and NARC-2011). Results of the present study indicated that wastewater negatively influenced the growth parameters and photosynthetic contents along with a significant increase in oxidative damage in terms of electrolyte leakage (EL) (50 and 61%), hydrogen peroxide (H2 O2 ) (52 and 61 μmol/g), and malondialdehyde (MDA) (16 and 17.7 μmol/g) contents in NARC-2009 and NARC-2011 respectively. However, bio-filtered water positively regulated the growth profile, activities of antioxidants such as superoxide dismutase (SOD), catalase (CAT), peroxidase (POD), total soluble sugars, amino acids, total protein, and proline contents in wheat as compared with untreated wastewater. In addition, bio-filtered water had significant impacts on the reduction of Cd, Ni, Pb, and Cu concentrations in roots, shoots, and grains of both wheat varieties as compared to wastewater. The concentrations (mg/kg) of Cd (15 and 18), Ni (35 and 57), Pb (5 and 7), and Cu (69 and 72) in roots, Cd (5 and 6), Ni (24 and 43), Pb (3 and 4), and Cu (16 and 19) in shoots, and Cd (0.7 and 1.0), Ni (11 and 26), Pb (2 and 3), and Cu (1.6 and 1.5) in grains of NARC-2009 and NARC-2011 were found under river wastewater treatment. Overall, wastewater treatment through bio-filtration process is an effective strategy for the reduction of toxic elements in bio-filtered water and their accumulation by plants. Highlights: River wastewater negatively influenced the growth attributes, physiological and defence profile of wheat plants. Biofilter reduced the heavy metals such as cadmium, nickel, lead, and copper contents in river wastewater and wheat plants. Biofiltered water potentially improved the growth and antioxidants activities in wheat as compared to river wastewater. Biofiltered water significantly reduced the heavy metals contents in different organs of wheat as compared to wastewater.